If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(X + 6) = 2(X + -2) Reorder the terms: 3(6 + X) = 2(X + -2) (6 * 3 + X * 3) = 2(X + -2) (18 + 3X) = 2(X + -2) Reorder the terms: 18 + 3X = 2(-2 + X) 18 + 3X = (-2 * 2 + X * 2) 18 + 3X = (-4 + 2X) Solving 18 + 3X = -4 + 2X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2X' to each side of the equation. 18 + 3X + -2X = -4 + 2X + -2X Combine like terms: 3X + -2X = 1X 18 + 1X = -4 + 2X + -2X Combine like terms: 2X + -2X = 0 18 + 1X = -4 + 0 18 + 1X = -4 Add '-18' to each side of the equation. 18 + -18 + 1X = -4 + -18 Combine like terms: 18 + -18 = 0 0 + 1X = -4 + -18 1X = -4 + -18 Combine like terms: -4 + -18 = -22 1X = -22 Divide each side by '1'. X = -22 Simplifying X = -22
| 6+12x=-5+5 | | 6(a+3)-10=-2(a+8) | | 3(x-8)=6(x+3) | | 6(a+3)-10=-2a+8 | | 10x+224-14x=188 | | X*x*7=63 | | 11=6m-1 | | W+48=-95 | | 8t^2+4t=0 | | 1-2(6-y)=y | | 10x-8=3x+3 | | 0.2z=3z | | -21b+10a=120 | | 4y+11=13 | | 3x+16-8x=19-14x+9x-3 | | 34g+17= | | X-45=108 | | 10a-21b=120 | | 700x^2+100x-16=0 | | 65-y=256 | | y=x^4-x^3+x^2-8 | | 6s-12=42s | | 6x+3y=2x+3 | | 6x+108=11-12 | | x*x+18=22 | | 4y+11=3y+4x | | (4a^2-3a+4)-(3a^2-7a+6)= | | (3a-7)+(4a+5)= | | 2(2x+3)=3(x-10) | | (2x+4)+(8x+6)=90 | | 3n-5=-48+-4n | | 5x-3x+16=x+8 |